SERCA2 Haploinsufficiency in a Mouse Model of Darier Disease Causes a Selective Predisposition to Heart Failure. (3rd May 2015) - Prasad, Vikram; Lorenz, John N.; Lasko, Valerie M.; Nieman, Michelle L.; Huang, Wei; Wang, Yigang; Wieczorek, David W.; Shull, Gary E.
Abstract : Null mutations in one copy of ATP2A2, the gene encoding sarco/endoplasmic reticulum Ca 2+ -ATPase isoform 2 (SERCA2), cause Darier disease in humans, a skin condition involving keratinocytes. Cardiac function appears to be unimpaired in Darier disease patients, with no evidence that SERCA2 haploinsufficiency itself causes heart disease. However, SERCA2 deficiency is widely considered a contributing factor in heart failure. We therefore analyzed Atp2a2 heterozygous mice to determine whether SERCA2 haploinsufficiency can exacerbate specific heart disease conditions. Despite reduced SERCA2a levels in heart, Atp2a2 heterozygous mice resembled humans in exhibiting normal cardiac physiology. When subjected to hypothyroidism or crossed with a transgenic model of reduced myofibrillar Ca 2+ -sensitivity, SERCA2 deficiency caused no enhancement of the disease state. However, when combined with a transgenic model of increased myofibrillar Ca 2+ -sensitivity, SERCA2 haploinsufficiency caused rapid onset of hypertrophy, decompensation, and death. These effects were associated with reduced expression of the antiapoptotic Hax1, increased levels of the proapoptotic genes Chop and Casp12, and evidence of perturbations in energy metabolism. These data reveal myofibrillar Ca 2+ -sensitivity to be an important determinant of the cardiac effects of SERCA2 haploinsufficiency and raise the possibility that Darier disease patients are more susceptible to heart failure under certain conditions.